2008
DOI: 10.1152/ajplung.00243.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Toll-like receptor 2 impairs hypoxic pulmonary vasoconstriction in mice

Abstract: Toll-like receptors (TLRs) mediate inflammation in sepsis, but their role in sepsis-induced respiratory failure is unknown. Hypoxic pulmonary vasoconstriction (HPV) is a unique vasoconstrictor response that diverts blood flow away from poorly ventilated lung regions. HPV is impaired in sepsis and after challenge with the TLR4 agonist lipopolysaccharide (LPS). Unlike TLR4 agonists, which are present only in Gram-negative bacteria, TLR2 agonists are ubiquitously expressed in all of the major classes of microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Humans and rats secrete 50% of the ammonia produced by the kidneys into the systemic circulation. (5,22) Under standard conditions, as in this study, ammonia secretion into the renal vein of mice amounts to 10 lmol/hour, but the 4-fold to 7-fold increased renal ammonia production and secretion during metabolic acidosis, (14,15) as develops during, e.g., septicemia, (23) would most likely render GS-KO/L or GS-KO/M mice hyperammonemic.…”
Section: Response Of Gs-deficient Mice To Ammonia Challengesmentioning
confidence: 49%
“…Humans and rats secrete 50% of the ammonia produced by the kidneys into the systemic circulation. (5,22) Under standard conditions, as in this study, ammonia secretion into the renal vein of mice amounts to 10 lmol/hour, but the 4-fold to 7-fold increased renal ammonia production and secretion during metabolic acidosis, (14,15) as develops during, e.g., septicemia, (23) would most likely render GS-KO/L or GS-KO/M mice hyperammonemic.…”
Section: Response Of Gs-deficient Mice To Ammonia Challengesmentioning
confidence: 49%
“…The endothelium participates in the septic response through the production of inflammatory mediators, up-regulation of adhesion molecules, modulation of coagulation pathways, and alteration of barrier functions (1,2). We previously found that bacterial lipoprotein TLR2 agonists, which are ubiquitously expressed by all bacteria that cause sepsis, induce endothelial inflammation and neutrophil adhesion to EC monolayers, increase lung neutrophil trafficking and respiratory dysfunction, and modulate the activity of several coagulation pathway intermediaries (16,20,45). The present studies delved into the signaling pathways involved in the TLR2-dependent activation of endothelial inflammation and modulation of coagulation pathway intermediaries.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that TLR2 activation modulates inflammatory effects of other TLR agonists, induces systemic, lung and myocardial inflammation in mice, and reduces contractility of cardiac myocytes in vitro (29–32). We have also found that TLR2 activation in vivo causes impaired vasoconstrictive responses to alveolar hypoxia and reduced arterial blood oxygenation (PaO 2 ) in mice (33). …”
Section: Introductionmentioning
confidence: 90%